Knowledge Management: A Literature Study on Management Opportunities in Information Technology - Puji Lestari (Institute of Information Technology and Social Science (IITSS), 2025)
Knowledge management has become a critical focus in the contemporary business landscape, particularly in the era of rapidly advancing information technology. It enables organizations to systematically collect, store, organize, and disseminate knowledge to enhance decision-making and performance. In the current digital environment, knowledge management plays an increasingly significant role in improving organizational performance, driving innovation, and strengthening competitive advantage. By implementing best practices and addressing potential challenges, information technology organizations can utilize knowledge management more effectively. Furthermore, the field continues to evolve alongside technological advancements, including the integration of artificial intelligence and advanced data analytics. Therefore, information technology companies must continuously update and refine their knowledge management practices to remain relevant and effective within the constantly changing technological landscape.